A retrospective study of umbilical artery S/D ratio assessment on color doppler for monitoring of fetal well-being in patients with intrauterine growth retardation and its correlation with perinatal outcomes - Bhatia, Shweta; Shah, Maitri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Intrauterine growth restriction (IUGR) is associated with an increased risk of perinatal morbidity, mortality and impaired neurodevelopment. The objective of this study is to evaluate the role of umbilical artery S/D ratio on color doppler for monitoring of fetal well-being in patient with intrauterine growth retardation and correlation with perinatal outcome. Methods: This retrospective observational study is carried out at a tertiary health care hospital over a period of 1 year. All clinically diagnosed cases of IUGR on the basis of fundal height are included in this study. The suspected cases of IUGR, color doppler tests were done to confirm the diagnosis of IUGR. The perinatal outcomes of the pregnancy of women with abnormal doppler parameters are then compared with women with normal Doppler parameters. Results: Out of the total sample size, 58.7% of the study population had abnormal doppler findings which were suggestive of IUGR, and 41.3% had normal doppler parameters. Our study showed that 18.2% newborns of study participants with abnormal S/D ratio had APGAR score at 5 minutes less than 7 as compared to 0% neonates of study participants with normal S/D ratio. This association was statistically significant. Also, statistically significant association was seen between 40 (90.9%) participants having abnormal S/D ratio whose neonates required NICU Admission as compared to 15 (48.4%) study participants having normal S/D ratio whose babies required NICU admission. Conclusions: Ultrasound examination and Doppler monitoring provide a non-invasive repetitive method for supervising fetuses with growth restriction in order to apply an adequate management.